Comparison of Conventional and Digital Impression Methods for Measuring Mesiodistal Teeth Dimensions: An Analytical Cross-sectional Study - Lam Nguyen Le; Khanh Phuong Vu Le (Dental Hypotheses)
Introduction: We aim to determine and compare the correlation between conventional and digital impression methods for measuring mesiodistal teeth dimensions. Methods: This cross-sectional analytical study was conducted on a total of 120 dental arch samples with less than 5 mm of tooth crowding, complete teeth on the dental arch, no missing teeth, and no fillings on the mesial or distal sides at Can Tho University of Medicine and Pharmacy. Conventional (extra-fast alginate) and digital impressions using a 3D intraoral scanner (CEREC Primescan) were taken from all participants, and the dimensions of the mesiodistal teeth were measured. Using R software, Pearson’s correlation coefficients were used to analyze the correlation between conventional and digital impression methods. Result: The pooled correlation for the maxilla was 0.8062 [95% confidence interval (CI): 0.7751–0.8334] (very strong positive correlation); for the mandibular, it was 0.7645 (95% CI: 0.7165–0.8054) (strong positive correlation), and for both jaws was 0.7863 (95% CI: 0.7581–0.8115) (strong positive correlation). Conclusion: In the Vietnamese population measurement of mesiodistal tooth width using a digital dental scanner can be used instead of conventional plaster models.